2010
DOI: 10.1371/journal.pone.0015261
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the C-Terminal Tail of HIV-1 gp41: Differential Exposure of the Kennedy Epitope on Cell and Viral Membranes

Abstract: The C-terminal tail (CTT) of the HIV-1 gp41 envelope (Env) protein is increasingly recognized as an important determinant of Env structure and functional properties, including fusogenicity and antigenicity. While the CTT has been commonly referred to as the “intracytoplasmic domain” based on the assumption of an exclusive localization inside the membrane lipid bilayer, early antigenicity studies and recent biochemical analyses have produced a credible case for surface exposure of specific CTT sequences, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 58 publications
4
56
0
Order By: Relevance
“…The HIR within gp41CTD of SIVmac239 is highly similar in location, if not in sequence, to the immunogenic region of the HIV-1 gp41CTD, the so-called "Kennedy epitope" (13,30,58). It was this high immunogenicity in HIV-1 which led to the proposal of an alternative topology featuring an extracellular loop (14,17,26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HIR within gp41CTD of SIVmac239 is highly similar in location, if not in sequence, to the immunogenic region of the HIV-1 gp41CTD, the so-called "Kennedy epitope" (13,30,58). It was this high immunogenicity in HIV-1 which led to the proposal of an alternative topology featuring an extracellular loop (14,17,26).…”
Section: Resultsmentioning
confidence: 99%
“…Proponents of the alternate model have addressed this inconsistency by suggesting that only a minority of Env molecules assume the conformation with an extracellular loop or that the immunogenic region is only exposed during or after fusion. This alternate model remains controversial; while Steckbeck et al (58) recently reported reactivity of antibodies against the immunogenic region on the surface of Env-expressing cells but not on intact virions, another recent study by Liu et al (34) found no conclusive evidence supporting the formation of an extracellular loop on Env-expressing cells.…”
mentioning
confidence: 99%
“…Further, based upon a model initially proposed in studies by Cleveland et al (11,52), the TM of MPER-TM1 construct could span the membrane twice; conflicting views exist regarding the degree of membrane spanning of the gp41 TM (28). The TM also appears to play a role in the overall exposure of the MPER, as selected amino-acid substitutions in this region of the TM affect binding by all three Nt MAbs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive Modeling of LLP Peptides Interaction with the Plasma Membrane-The three LLP motifs of the CTT of gp41 have been suggested to interact with the plasma membrane (9,(22)(23)(24)(25)(26)(27)(28), although the depth and orientation of their insertion inside the phospholipid bilayer has not been described. Recently the computational modeling of the E z potential has been described as the ability of peptides to insert into lipid membranes (15,16).…”
Section: Design Of the Llp Arginine To Lysinementioning
confidence: 99%